Developing of innovative and cool mobile applications on the Googles Android powered devices 5 - Arun Mohan (2014)
Sports Info is an interactive sports app developed using Google’s Android Platform featuring polls, news, scores and pictures. It covers most major sports including cricket, rugby, soccer, tennis etc. The app will include an opinion poll section that enables users to give their opinions on different topics and questions and the statistical results will be displayed and can be shared through social networks. It will also include a news section in which up to date headlines and major stories will be featured. Users will be able to subscribe their favourite sports and the app will deliver the relevant information according to their choice. Users will get notifications about all major upcoming matches relevant to their choice of sports. Sports Info is tailored to meet the expectations of smart phone users who regularly checks sports updates like match schedules, score card and important sports news.